Os estilos de liderança nas organizações não governamentais da região metropolitana de Belém - Santos, Ticiane Lima dos (2010)
This study aimed to analyze the leadership style adopted by managers of nongovernmental organizations in the metropolitan region of Belem on the theory of Hersey and Blanchard. This theory is called situational leadership ranks E1, E2, E3, E4 and the styles of leadership and maturity in parallel classes M1, M2, M3 and M4. This study examined the relationship of leadership styles with the maturity of work, identified the relationship of leadership styles as related to psychological maturity and job maturity and psychological maturity. The main objectives were to analyze and relate leadership styles with the maturity of the leaders and understand the phenomenon of leadership from the self-perception of those who lead the organizations studied. To achieve the objectives we used a questionnaire already validated the theory of situational leadership and applied in 320 non-governmental organizations in the metropolitan region of Belem The methodology was quantitative, descriptive and exploratory. The analysis was by descriptive statistics and inferential statistics for univariate and bivariate form, applying the chi-square, the V Crammer and Spearman correlation. The data analysis shows safety, attested to the frequencies, and average margin of error and after application of the tests it was found that a relationship between the leadership style of work with the maturity and psychological maturity. The managers of nongovernmental organizations practicing various styles of leadership and focus on the quadrant of high maturity. It was diagnosed when the manager uses only one style of leadership was the predominance of E3 "share or support", which represents 24% of the sample. As uses two styles of leadership is the predominance of E3 and E2, which represents 76%. So the managers of nongovernmental organizations in the metropolitan region of Belem, practicing a style of leadership support, sharing ideas for decision making using a democratic style